Permainan Tradisional Dakon sebagai Intervensi pada Anak Diskalkulia - Ama, Heronimus Dappa; Bessu, Lidia Vera (Universitas Muhammadiyah Magelang, 2026)
This study aims to test the effectiveness of the traditional dakon game in improving children's numeracy skills. The study involved 15 kindergarten students in Loura District, Sumba, as research subjects. The study used a quantitative research method with a quasi-experimental pretest-posttest design. Data were collected using observation sheets. Data were analyzed using the Shapiro-Wilk normality assumption test (priority for n < 50), followed by a paired samples t-test (SPSS IBM, α = 0.05, two-tailed) to test the difference in pretest-posttest means. The normality test showed that the data were normally distributed. The paired t-test showed a significant difference between the pretest and posttest. These findings indicate that the traditional dakon game can improve the numeracy skills of children with dyscalculia. Therefore, the traditional dakon game can be a learning tool to introduce and improve the numeracy skills of children with dyscalculia.